2016
DOI: 10.1007/s00726-015-2158-z
|View full text |Cite
|
Sign up to set email alerts
|

Structure–activity relations of leucine derivatives reveal critical moieties for cellular uptake and activation of mTORC1-mediated signaling

Abstract: Among amino acids, leucine is a potential signaling molecule to regulate cell growth and metabolism by activating mechanistic target of rapamycin complex 1 (mTORC1). To reveal the critical structures of leucine molecule to activate mTORC1, we examined the structure-activity relationships of leucine derivatives in HeLa S3 cells for cellular uptake and for the induction of phosphorylation of p70 ribosomal S6 kinase 1 (p70S6K), a downstream effector of mTORC1. The activation of mTORC1 by leucine and its derivativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

14
70
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 52 publications
14
70
0
Order By: Relevance
“…Lately, this story has become further convoluted as Nagamori et al reported that several carboxylic esters and a hydroxamic acid derivative of L -leucine were LAT1 substrates. 32 Their conclusions, based in part on a trans -stimulation assay, 36 contradicted previous reports that esters do not bind LAT1. 4, 24, 37 …”
mentioning
confidence: 85%
See 4 more Smart Citations
“…Lately, this story has become further convoluted as Nagamori et al reported that several carboxylic esters and a hydroxamic acid derivative of L -leucine were LAT1 substrates. 32 Their conclusions, based in part on a trans -stimulation assay, 36 contradicted previous reports that esters do not bind LAT1. 4, 24, 37 …”
mentioning
confidence: 85%
“…And to further probe the SAR for close-in derivatives of the HA’s (Table 2), we also decided to test the structurally-related primary amide Leucinamide 13e . Though ester 9e was recently reported to be a LAT1 substrate, 32 to our knowledge this was the first time that 13e or any amino acid primary amide has been tested for LAT1 activity. Interestingly, 13e did not demonstrate significant substrate activity (efflux rate: 0.69 fmol/min).…”
mentioning
confidence: 88%
See 3 more Smart Citations